Impact of seasonal changes on root-associated microbial communities among phreatophytes of three basins in desert ecosystem - Zhang, Yulin; Du, Yi; Mu, Zhaobin; Islam, Waqar; Zeng, Fanjiang; Gonzalez, Norela C. T.; Zhang, Zhihao (Frontiers in Plant Science, 2025)
Seasons often alter climate conditions and affect nutrient cycling by altering plant physiology and microbial dynamics. Plant growth and health depend on a symbiotic relationship with root microbes, however, the root-associated microbiota is key to plant evolution and ecosystem function. Seasonal changes in root-associated microbiome diversity and composition of desert plants are vital for understanding plant adaptation in desert ecosystems. We employed high-throughput sequencing to investigate the seasonal dynamics of root-associated microbial communities, including the root endosphere (RE), rhizosphere soil (RS), and bulk soil (BS), across three basins in Xinjiang, China: Turpan, Tarim, and Dzungaria. Proteobacteria dominated bacterial communities in different seasons, while Ascomycota prevailed in fungi. The spring and summer conditions favor greater microbial differentiation. The RE, RS, and BS bacterial communities in May (spring) showed a noticeable absence of highly connected nodes within and between modules. However, the opposite trend was observed in July (summer) and September (autumn). The community assembly of root-associated microbiome (bacteria and fungi) in different seasons primarily followed a random process. Random forest analysis found that seasonal variations in RE bacterial communities were primarily influenced by scattered radiation, while fungal communities were mainly affected by soil available potassium. Environmental factors affect the BS bacterial community more than the fungal community across different seasons. A structural equation model revealed temperature and precipitation’s direct effects on microbial communities, mediated by soil and root nutrient availability. Soil pH and EC predominantly affected root bacterial communities, not fungal communities. The fungal community within the RE was found to be directly influenced by seasonal shifts, whereas the RS fungal community composition was significantly impacted by changes in precipitation patterns driven by seasonal variation. The climate seems to be a crucial factor in influencing the dynamic of the root microbiome in desert plants, surpassing the influence of soil and root nutrient availability. This study underscores seasonal root-associated microbiome variations and their important roles in desert ecosystem functions.